A pilot study of cognitive behavioural therapy integrated with activity pacing for fatigued breast cancer patients undergoing chemotherapy in Ethiopia - Getu, Mikiyas Amare; Chen, Changying; Addissie, Adamu; Seife, Edom; Wang, Panpan; Kantelhardt, Eva Johanna (Frontiers in Oncology, 2022)
Background Fatigue is a common symptom in breast cancer patients, and it is one of the major factors that influence the quality of life (QoL). Cognitive behavioural therapy (CBT) has been recommended to manage cancer-related fatigue. In this study, CBT will be integrated with activity pacing (AP), which can help breast cancer patients achieve a balance between activity and rest. Therefore, this pilot study aimed to investigate the acceptability, feasibility, and efficacy of the CBT-AP intervention. Methods A total of 10 fatigued breast cancer patients undergoing chemotherapy were included in the study. The acceptability and feasibility of the study were measured by the patient recruitment rate, attrition rate, intervention fidelity, intervention compliance, and therapist’s and participant’s evaluations of the intervention. The outcomes were measured at baseline and at 6 weeks of intervention. Results The pre–post study suggested that CBT-AP was found to be acceptable and feasible for fatigued breast cancer patients undergoing chemotherapy. Among 27 eligible participants, 10 (37.03%) participants accepted our invitation to participate in the study. One participant dropped out from the intervention because of serious illness, and the dropout rate was 10%. Both the intervention fidelity and intervention compliance were found to be satisfactory. Fatigue severity [Brief Fatigue Inventory (BFI)] was reduced in 77.77% of participants from baseline to 6 weeks of intervention. The global health status/QoL scale and physical, emotional, and social functioning scales were improved from baseline to 6 weeks of intervention. All symptom scales, except constipation, diarrhea, and financial difficulties, were decreased after the intervention. Depression [Public Health Questionnaire (PHQ)-9] was reduced in 55.55% of participants. Conclusion This study suggested that CBT-AP is an acceptable, feasible, and potentially efficacious intervention to reduce fatigue and improve the QoL of breast cancer patients. The efficacy of a CBT-AP programme is going to be investigated in subsequent larger randomized clinical trials.